Alocação de recursos: nível ótimo de diversificação intraclasse entre fundos de investimentos abertos no Brasil - Duba, Tiago Lacerda Nader (2013)
Despite the diversity of their strategies, the returns of hedge funds generally exhibit a positive correlation with stock index. On the other hand, distinct funds categories tend to be less correlated to each other compared to funds from the same category. The idea of diversification between funds with low correlation is discussed repeatedly in the literature. In practice, however, few portfolios allocators optimize their portfolios guided by Markowitz (1953) for example. The aim of this study is to identify the optimum asset diversification within the same category. The methodology will seek to minimize the idiosyncratic risk of the investment funds through simulations with other funds in the same category. The study contains analyzes for choosing the optimal number of assets (investment funds) in a given portfolio. These results would benefit mainly the decision making process of Wealth Managements, Investment Consulter and Private Bankers.